Coaching practiced - Tee, David; Passmore, Jonathan (BPS textbooks in psychology., 2022)
"The first two decades of the third millennium have witnessed a proliferation of coaching psychology approaches. These approaches have extended the original modules developed in the 1980s and 1990s such as GROW and Co-Active coaching into new territories. Many of these new approaches have been drawn from the therapeutic and counselling domain; these initially included cognitive behavioural coaching, solution focused coaching, and psychodynamic coaching during the 2000-2010 period. This was followed by a more diverse range of models including the Motivational Interviewing, Acceptance and Commitment coaching, Compassion-based coaching and Gestalt, which have each been developed for use in coaching. In the period post-2020, other models are also now being considered as possible frameworks for use with coaching clients in non-clinical relationships, such as dialectical behavioural therapy and meta-cognitive therapy (for a wider discussion of third wave CBC see Passmore & Leach, 2022). In addition to the influences from therapy, psychological models have also been translated for use in coaching psychology practice, such as positive psychology and mindfulness. This flow of models from therapy and psychology contrasts with the relative sparse influence from change management and organisational development, with Appreciative coaching being a rare exception drawing on Appreciative Inquiry as a structure to frame positive-focused conversations. This multiplicity of available frameworks can be confusing for the coach. Some have responded by focusing on a single model or framework as a way to structure all conversations. However, the evidence suggests the majority have adopted a more eclectic approach and have sought to integrate a range of different models into their work with clients. This follows suggestions from writers in the emerging years of coaching, such as Alison Hardingham (2006) and Jonathan Passmore (2006), who advocated for a more eclectic approach, by which the coach should draw from a number of different streams and, in doing so, would be best able to respond to the unique individual and their specific presenting issue, as opposed to forcing each client to become the round peg required to fit the shape and size of 'hole' offered by the coach. These ideas of eclectic approaches have been further developed (Hardingham, 2021; Passmore, 2021), with an emphasis on each coach developing their own distinctive evidenced-based approach informed by the cultural context, types of clients and their own personal style to build an approach which is informed by science but which can be flexed and adapted to meet the client where they are"--